The true future of the open future - Loss, R. (2012)
This thesis defends the 'true-futurist' view, according to which statements about the future are either true or false, even if the future is open and unsettled in some robust, objective and mind-independent sense. A general argument for the validity of the principle of bivalence in the open future is advanced. The key feature of such argument is the 'principle of retrospective determinacy', stating that, for any proposition p, if it is now the case that p, then it was true that p would be the case. Different possible objections are discussed and dismissed. Second, two true-futurist theories are presented and shown to meet all the relevant desiderata of a true-futurist theory. In particular, much attention is devoted to the 'problem of counterfactual evaluation', concerning the truth-value of future-contingent statements in merely counterfactual scenarios. In addition, it is argued that that the choice between the two true-futurist theories depends upon which metaphysical picture of time is assumed as true. Some notable theoretical commitments of True-Futurism are examined. In particular, it is argued that True-Futurism is incompatible with two different ideas. The first one being that future-contingent statements (although bivalent) have an indefinite truth-value. The second one being that there are true 'counterfactuals of openness', stating that a certain future-contingent statement would have had a specific truth-value, had different circumstances obtained.